Cover Image, Volume 28, Issue 10. (11th October 2017) - Ho, Gordon; Villongco, Christopher T.; Yousefian, Omid; Bradshaw, Aaron; Nguyen, Andrew; Faiwiszewski, Yonatan; Hayase, Justin; Rappel, Wouter‐Jan; McCulloch, Andrew D.; Krummen, David E.
Abstract : On the cover : The cover image, by Gordon Ho MD et al., is based on the Original Article Rotors exhibit greater surface ECG variation during ventricular fibrillation than focal sources due to wavebreak, secondary rotors, and meander, DOI: 10.1111/jce.13283 .